Normal congruences with focal bicylindrical surfaces - Koneva, N. P. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
A system of equations determining normal con~uences with focal surfaces (bicylinders) is found in abiaxial space of hyperbolic type by using a moving frame of the space and the method of Cartan exteriorforms. The geometric construction of these congruences is presented.